The Association of Current Knowledge, Involvement and Confidence Levels on Gene-Based Nutrition Services among Nutrition Workers in Indonesia: Hubungan Pengetahuan tentang Pelayanan Gizi Berbasis Gen dengan Keterlibatan dan Kepercayaan Diri Tenaga Gizi di Indonesia - Farhan, Alfina Ulfah; Hafizhah, Rafiqah Dwita; Aji, Arif Sabta; Kurniasari, Yulinda; Herawati, Herni Dwi; Zulfa, Ifana Fitria; Putri, Sintia Aurilia; Alfiana, Rina (Amerta Nutrition, 2024)
Background: The knowledge, involvement, and self-confidence of nutrition professionals are highly required in the implementation of gene-based nutrition services. The limited number of nutrition professionals applying gene-based nutrition services poses a unique challenge in the developmental process of gene-based nutrition services in Indonesia. Objectives: This study aims to identify the association between the knowledge, engagement, and confidence levels of nutrition workers with gene-based nutrition services in Indonesia. Methods: This cross-sectional study was conducted in May-June 2023. The participants consisted of nutrition workers from five provinces in Indonesia. The instrument of this study used structured questionnaires encompassing socio-demographic information, knowledge, engagement, and confidence levels of nutrition workers distributed using the Qualtrics Survey platform. Data analysis employed the chi-square test with the help of Statistical Package for the Social Sciences (SPSS) version 25.0. Results: This study involved a total of 423 respondents. Findings indicated that 53.4% of nutrition workers possessed limited knowledge, 60.0% exhibited minimal engagement, and 51.8% held low confidence levels in gene-based nutrition services. Notably, a significant correlation was identified between knowledge and confidence in gene-based nutrition services (p=0.001; PR=2.0; CI=1.35-2.94). Additionally, a significant association was present between knowledge and engagement in gene-based nutrition services (p=0.001; PR=2.00; CI=1.34-2.96). Conclusions: This study highlights the association of low nutritionists' knowledge with low personal involvement and confidence levels to gene-based nutrition services in Indonesia. Nutrition professionals are encouraged to enhance their grasp of genetics and its relevance to nutrition through dedicated training, participation in seminars, and ongoing education initiatives.